Verbal autopsy to determine the timing and causes of infant deaths in the northern state of India - Parashar, Anupam; Barall, Deepesh; Gupta, Anmol; Chauhan, Tripti; Kumar, Devender; Kumar, Arvind; Kumar, Sanjay; Sharma, Gopal Ashish; Kumari, Sunita (International Journal of Contemporary Pediatrics, 2017)
Background: Data on timing and probable causes of infant deaths are very important for the design of intervention to reduce mortality because of very limited study in the state. This study was undertaken to determine the timing and causes of infant deaths in our state using verbal autopsy. The suggestions and recommendations can be used to strengthen and improve the existing facilities and services for the better outcome of life in the early childhood. Methods: A cross sectional study was conducted in 180 selected clusters by WHO cluster sampling method, using validated verbal autopsy tool for timing and causes of infant deaths. Results: Verbal autopsy was done for 45 infant deaths. 37.8% infant deaths were early neonatal, 15.5% in late neonatal and 46.7% in post neonatal period with mean age of 5.79±6.35 days in neonatal period while it was 5.07±3.38 months in post neonatal period. Of all the infants 57.78% were females. The major causes of death were severe infection (15.5%) in neonates, pneumonia (13.3%) in post neonates followed by LBW with prematurity (11.1%) and diarrhea (11.1%). No specific cause could be determined in 13.3% cases. Conclusions: The major causes of infant deaths are preventable. It emphasizes for the robust reporting mechanism to determine the exact causes of all infant mortality, strengthening of comprehensive health care delivery and ensuring the accessibility to the health care services to have a healthy infanthood.